PERCEPTIONS, TENDANCES ET PRÉFÉRENCES EN FORESTERIE URBAINE: CAS DE LA VILLE DE LOMÉ AU TOGO - Polorigni, Botolisam; Radji, Raoufou; Kokou, Kouami (European Scientific Journal, ESJ, 2014)
Opportunities for forestry in urban areas can be analyzed in relation to urban, their lives, their priorities and their views on urban trees, then consider the conditions under which trees can promote them. This study is an inventory of green spaces in Lomé. It evaluates its floristic diversity and identifies the population’s perceptions and expectations in urban forestry. The inventory of green spaces made indicates that each inhabitant of the urban agglomeration of Lomé has 0.75 m² of green space while is less than 10 m² recommended by the World Health Organization (WHO) in urban areas. In total, 93 species belonging to 79 genera and 47 botanical families were identified. People perceive very well the role and the importance of trees in urban and suburban areas. The main role is recognized embellishment (61%), to which are added other benefits such as aesthetics (33%), improvement of living conditions (4%). Only 2% of urban trees are used as medicine in Lomé. Sixty-one percent of respondents stated attend greenspace. These concerns of the people are not to be neglected and should be taken into account in future development planning actions in urban and peri-urban forestry.